How Much does Work Matter for Inequality? Time, Money and Inequality in International Perspective - Lars Osberg (Luxembourg Income Study (LIS), 2002)
How much of the difference between countries in inequality of the distribution of income can be explained by work - i.e. by differing probabilities of any employment? Across OECD countries there are large differences in the average level and distribution of working hours. These differences arise from differing common entitlements to leisure (e.g. paid Public Holidays), plus differences in working hours per employee and in the percentage of the working age population who have some paid employment. The participation level is particularly important for inequality differences and there is persuasive evidence that country attitudes to paid employment, particularly for women, differ significantly. This paper uses Luxembourg Income Study data on Canada and the USA, UK, Germany, France and Sweden to simulate the income distributions that other countries would have if they had the Canadian pattern of workforce participation. Because employment rates in the US are quite similar to those in Canada, inequality in the USA would change only fractionally. In every other case, poverty and inequality would fall, indicating that measured differences in the inequality of money income between the North America and Europe understate the extent of cross country differences in well being. Put simply, in North America the relatively poor have to work harder, and still end up poorer, than in Europe.
Keywords: 330; Einkommensverteilung; Erwerbstätigkeit; Arbeitszeit; Erwerbstätigkeit; Weibliche Arbeitskräfte; Kanada; USA; Deutschland; Frankreich; Großbritannien; Schweden